REVITALISASI TUDANG SIPULUNG SEBAGAI MEDIA KOMUNIKASI VERTIKAL ANTARA MASYARAKAT DAN PEMERINTAH DI KABUPATEN BONE - Yunda, Andi Atrianingsi; Mirsa, Sitti; Wardah, Wardah (JPP (Jurnal Politik Profetik), 2018)
Tudang sipulung is a routine farmer meeting held in Bone. The meeting is held twice a year, namely rendengan season (i.e.Aapril-October month and Gadu Season (i.e September-March). The implementation of Tudang Sipulung begans from the village and the sub district level and up to the district level. The aim of this research is was to observe the revitalization of the tudang sipulung as a vertical communication media between the goverment and the community in Bone Regency.  The result of this research indicated that tudang sipulung as a media of vertical communication between the goverment and the community has not shown maximun result because of the communication distortion  between the goverment and the community that is still  lack of openness in communication.  It is Expected though the implemantation of the Tudang sipulung management in the future can be even better, especially for vertical ccommunication between the goverment and the community, to be more open considering this meeting is held for the common good.